2018
DOI: 10.1177/0093650218800915
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Motivations for Online Privacy Protection Behavior: Insights From Panel Data

Abstract: Personally managing and protecting online privacy has become an essential part of everyday life. This research draws on the protection motivation theory (PMT) to investigate privacy protective behavior online. A two-wave panel study (N = 928) shows that (1) people rarely to occasionally protect their online privacy and (2) people most often delete cookies and browser history or decline cookies to protect their online privacy. In addition, (3) the perceived threat is high: People perceive the collection, usage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(146 citation statements)
references
References 56 publications
7
135
1
3
Order By: Relevance
“…In the health context, perceived severity of a disease has indeed been shown as a trigger of protection motivation (Katz et al, 2009). Similar findings have been concluded in the context of general privacy protection (Boerman et al, 2018): consumers who consider data collection online a problem, are more motivated to protect themselves.…”
Section: Knowledge and Perceived Severity Of And Susceptibility To Dasupporting
confidence: 66%
See 2 more Smart Citations
“…In the health context, perceived severity of a disease has indeed been shown as a trigger of protection motivation (Katz et al, 2009). Similar findings have been concluded in the context of general privacy protection (Boerman et al, 2018): consumers who consider data collection online a problem, are more motivated to protect themselves.…”
Section: Knowledge and Perceived Severity Of And Susceptibility To Dasupporting
confidence: 66%
“…While the impact of self-efficacy has been widely investigated in the online data protection context, response efficacy has received considerably less attention. Boerman et al, (2018) showed the significant positive impact of response efficacy on protection motivation for different types of online privacy protection. In fact, technical knowledge how data is collected and used puts consumers in the position to be able to ask the follow up question: how to protect myself, and consider their options, e.g., the opt-out functions offered by AdChoices and Google.…”
Section: Knowledge and Perceived Self-efficacy And Efficacy Of Opt-oumentioning
confidence: 96%
See 1 more Smart Citation
“…Young reported in his study, that "older individuals tended to report using ad blockers less [than younger individuals]" (Young, 2016). In another research it has been stated that there are no significant differences younger and older adults with respect to privacy concerns and privacy protective behaviors (Boerman et al, 2018)-both motivational factors for the usage of ad blockers as stated before. A significant difference was shown by Zhao et al, which stated that "people who are younger than 34 are more likely to use ad blockers" (Zhao et al, 2017).…”
Section: Age and Ad Blocker Usagementioning
confidence: 76%
“…Researches in the behavioral field contains researches into the identification of factors influencing the usage of ad blockers. The most important factors leading the use of ad blocker are the needs for security/privacy, for avoiding further interruption online and for page loading speed (Boerman, Kruikemeier, & Zuiderveen Borgesius, 2018;Brinson et al, 2018;Mccoy, Everard, Polak, & Galletta, 2007;Redondo & Aznar, 2018;Zhao et al, 2017).…”
Section: Ad Blockermentioning
confidence: 99%